Treatment outcomes and associated factors among tuberculosis patients attending Gurage Zone Public Hospital, Southern Nations, Nationalities, and People's Region, Ethiopia: an institution-based cross-sectional study - Agazhu, Haile Workye; Assefa, Zebene Mekonnen; Beshir, Masino Tessu; Tadesse, Habtam; Mengstie, Aregash Sitot (Frontiers in Medicine, 2023)
Background: Tuberculosis remains the most important global health problem. Globally, Tuberculosis is the cause of a single infectious agent and the ninth leading cause of death ranking above human immunodeficiency virus. In high-burden settings, one of the mechanisms to control tuberculosis is to identify patients' problems during treatment. Nevertheless, the problem is still a countrywide issue, and there is a shortage of research to show treatment outcomes and associated factors of tuberculosis in Southern nation nationalities and people's regions in the Gurage Zone.: Institution-based, cross-sectional study was conducted to collect data among 347 medical records of tuberculosis patients from July 20, 2016, up to July 30, 2021, at Gurage Zone Public Hospitals. The tool includes data about socio-demographic characteristics, tuberculosisrelated, and tuberculosis treatment outcome status. The data were analyzed using SPSS version 26 and, multivariable logistic regression analyses were undertaken to identify significantly associated variables with successful tuberculosis treatment outcomes. The adjusted odds ratio (AOR) with its 95% confidence interval (CI) at a p-value of < 0.05 was used to claim statistical association.Results: In this study, the overall prevalence of successful tuberculosis treatment outcomes was 79.3%. HIV-negative tuberculosis patients (AOR=4.33; 95% CI: 1.91, 9.79), patients the age of < 20 years (AOR =0.16; 95% CI: 0.04, 0.74), and married participants (AOR=0.29; 95% CI: 0.10, 0.88) were significantly associated with successful tuberculosis treatment outcomes.Conclusions and recommendations: the prevalence of successful tuberculosis treatment outcomes was low. HIV-TB co-infected, single marital status and age >20 years negatively affected the treatment outcomes of tuberculosis so more effort and better attention should be given to better outcomes of tuberculosis patients especially for HIV-TB co-infected participants.